R&D subsidies, innovation location, and productivity growth - Colin R. Davis; Ken'ichi Hashimoto (Osaka University, Institute of Social and Economic Research (ISER), 2023)
This paper studies how national research subsidies affect productivity growth and national welfare through adjustments in the geographic location of research and development (R&D) across countries. Our two-country framework features a tension in the firm-level innovation location decision between accessing technical knowledge and sourcing low-cost high-skilled labor. With trade costs and imperfect international knowledge diffusion, the larger country has a greater share of industry and tends to host a larger share of innovation. In this setting, we find that an R&D subsidy expands the implementing country's share of innovation and raises the rate of productivity growth. Although the non-implementing country experiences a welfare improvement, the rising cost of the policy generates a concave relationship between the R&D subsidy and the welfare of the implementing country, yielding an optimal R&D subsidy rate.
Keywords: F12; F43; R11; 330; Optimal R&D Subsidies; Industry and Innovation Location patterns; Endogenous Productivity Growth; Endogenous Market Structure